'Corruption is Dirt': Metaphors for Political Corruption in the Spanish Press. Issue 3 (1st April 2015) - NEGRO, ISABEL
<x content-type="archive" xml:space="preserve">Abstract</x> Corruption seems to have been a fact of Spanish politics in recent years, involving property deals, local government and political parties. The latest scandal, known as the 'Bárcenas affair', involved the conservative ruling party. Set within the theoretical framework of Conceptual Metaphor Theory, this paper seeks to explore the conceptualization of corruption in Spanish through the analysis of the linguistic and verbo–pictorial metaphors used in the Spanish press to tackle the issue of corruption and the Bárcenas case. We will see that the view of corruption is shaped by a number of conceptual metaphors. Like all political metaphors, corruption metaphors make an abstract concept more tangible. The study also shows how metaphor works in actual discourse, thus providing an insight into the pragmatic function of metaphor (Charteris-Black 2004, 2005). In this light, it is argued that the various metaphors structuring corruption carry a strong axiological weight by providing a negative evaluation of political corruption.